2015
DOI: 10.1039/c5an00775e
|View full text |Cite
|
Sign up to set email alerts
|

Isoreticular bio-MOF 100–102 coated solid-phase microextraction fibers for fast and sensitive determination of organic pollutants by the pore structure dominated mechanism

Abstract: Here we report the successful utilization of the stepwise ligand exchange strategy for the improvement of adsorption ability of a series of bio-MOFs. The fast extraction rate and the different adsorption performances of the three bio-MOF coatings were dominated by their pore structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 36 publications
(72 reference statements)
1
15
0
Order By: Relevance
“…Liu et al [155] also observed good compatibility between the simulated results and experimental results.…”
Section: Mofssupporting
confidence: 66%
See 1 more Smart Citation
“…Liu et al [155] also observed good compatibility between the simulated results and experimental results.…”
Section: Mofssupporting
confidence: 66%
“…On the other hand, MOFs, which are sensitive to humidity, can be protected by other humidity-resistant materials for guaranteeing their applications. For example, after covering bio-MOFs with silicone glue, the fibers were used for DI SPME in aqueous samples [155]. In another study [158], IRMOF-3, which is very sensitive to humidity, was used in the headspace of aqueous samples after being protected with ionic liquid and polydimethylsiloxane (PDMS).…”
Section: Mofsmentioning
confidence: 99%
“…As mentioned in Section 3.1, commercial f-SPME devices with solid materials require a liquid polymer to attach the stationary phase to the core. This justifies the use of glues to attach the MOF coatings to the stainless-steel wires in a high number of studies [47,66,67,81,82,85,86,88,89,[107][108][109][110][111][112][113], or even to fused silica [68]. The sealant is used in an amount that it does not block the pores of the solid sorbent and it does not participate in the extraction process [32,55].…”
Section: Preparation Of Mof-based F-spme Devicesmentioning
confidence: 99%
“…The DI-SPME-GC methods with these fibers has been used for the analysis of water samples coming from different sources [62,81,85,88,96,104,105,107,109,113], aqueous extracts of foods [85,87,90], and aqueous extracts of soils [62,104,105]. PAHs [62,81,85,96,104,105,107,109] and pesticides [90,107,113] have been the most common analytes determined with the developed methods using the DI mode.…”
Section: Analytical Performance Of Mof-based F-spme Devicesmentioning
confidence: 99%
“…Only Liu et al. prepared bio‐MOF 100–102 coated solid‐phase microextraction fibers for extraction of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%